Точний висів просапних культур – першочерговий крок у програмуванні майбутнього врожаю - Васильковська, К. В.; Vasilkovska, Katherina (КНТУ, 2015)
Визначено, що першочерговим кроком у програмуванні майбутнього врожаю просапних культур є точний висів насіння. Запропоновано конструкцію нового пневмомеханічного висівного апарату для точного висіву насіння просапних культур з периферійним розташуванням комірок на висівному диску та пасивним пристроєм для видалення зайвого насіння відцентровим способом. Проведені дослідження запропонованого висівного апарата в ґрунтовому каналі, які підтвердили його високу продуктивність і якість висіву. The basis of technologies for production of crops is crop programming, which includes system maintaining and protection of soil fertility, training of high-quality seed, mechanization and automation of production, protection of plants from diseases, pests and weeds. First priority step in programming future crop cultivated crops - is exact seeding, that ensure uniform seed placement by area of feed. To enhance the effectiveness precision seeding row crops at the Department of Agricultural Engineering Kirovohrad National Technical University have developed and made prototype of a new pneumomechanical seed distribution vehicle for precise seeding of cultivated crops with a peripheral cells to seed disk and a passive device to remove superfluous seeds centrifugal method. Research proposed sowing device channel in the ground showed that the proposed device allows seed: get uniformly placed in the seed row, dosed sugar beet seeds and corn without changing disk sowing apparatus, reduce the use of seed.
Exact seeding cultivated crops – priority steps in the programming the future harvest
Keywords: програмування врожаю; точний висів; насіння; пневмомеханічний висівний апарат; programming a crop; accurate sowing seeds; pneumomechanical seed distribution vehicle